Related factors for depression among Chinese men who have sex with men: A protocol for systematic review and meta-analysis. Issue 7 (19th February 2021) - Zheng, Yuping; Gao, Jing; Jiang, Xiaolin
Abstract: Background: Men who have sex with men (MSM) are the focus group of acquired immune deficiency syndrome intervention, because of the impact of social concepts, they suffer from a lot of social discrimination, and mental health problems are more prominent. Depression is prevalent in Chinese MSM. The aim of this systematic review is to systematically assess the current evidence on factors associated with depression among Chinese MSM. Methods: This study will be conducted in strict accordance with the preferred reporting items for systematic reviews and meta-analysis protocols. China National Knowledge Infrastructure, VIP Database, Wanfang Database, Chinese Biomedical Literature Database, PubMed, Embase, Web of Science, and the Cochrane Library will be searched comprehensively to collect cross-sectional studies, case-control studies, Cohort studies for depression of the related factors among Chinese MSM. The retrieval time is limited from the establishment of the database to December 2020. Two researchers independently evaluate the study and extract the data according to the inclusion and exclusion criteria. Meanwhile, the Newcastle–Ottawa scale and the bias risk assessment criteria of the agency for healthcare research and quality will be used to evaluate the risk of bias in the included studies, and the meta-analysis will be carried out by using Stata 15.0. Results: This study will systematically evaluate the related factors for depression among Chinese MSM based on published studies. The results will be presented here. Conclusion: The conclusion of the systematic review and meta-analysis will provide clinical evidence for the related factors and prevention and treatment measures of depression among Chinese MSM.